Valence band offset of β-Ga(2)O(3)/wurtzite GaN heterostructure measured by X-ray photoelectron spectroscopy - Wei, Wei (Springer, 2012)
A sample of the β-Ga(2)O(3)/wurtzite GaN heterostructure has been grown by dry thermal oxidation of GaN on a sapphire substrate. X-ray diffraction measurements show that the β-Ga(2)O(3) layer was formed epitaxially on GaN. The valence band offset of the β-Ga(2)O(3)/wurtzite GaN heterostructure is measured by X-ray photoelectron spectroscopy. It is demonstrated that the valence band of the β-Ga(2)O(3)/GaN structure is 1.40 ± 0.08 eV.